Early‐onset hypertension associated with extensive cutaneous capillary malformations harboring postzygotic variants in GNAQ and GNA11. Issue 6 (10th August 2022) - Davies, Olivia M. T.; Ng, Ashley T.; Tran, Jennifer; Blumenthal, Shoshana; Arkin, Lisa M.; Nopper, Amy J.; Cottrell, Catherine E.; Garzon, Maria; Siegel, Dawn H.; Frieden, Ilona J.; Drolet, Beth A.
Abstract: Background and Objectives: Cutaneous capillary malformations (CMs) describe a group of vascular birthmarks with heterogeneous presentations. CMs may present as an isolated finding or with other associations, including glaucoma and leptomeningeal angiomatosis (i.e., Sturge–Weber syndrome) or pigmentary birthmarks (i.e., phakomatosis pigmentovascularis). The use of targeted genetic sequencing has revealed that postzygotic somatic variations in GNAQ and GNA11 at codon 183 are associated with CMs. We report five patients with early‐onset hypertension and discuss possible pathogenesis of hypertension. Methods: Twenty‐nine patients with CMs, confirmed GNAQ/11 postzygotic variants, and documented past medical history were identified from a multi‐institutional vascular anomalies study. Early‐onset hypertension was defined as hypertension before the age of 55 years. Clinical data were reviewed for evidence of hypertension, such as documentation of diagnosis or elevated blood pressure measurements. Results: Five of the 29 patients identified as having GNAQ/11 postzygotic variants had documented early‐onset hypertension. Three individuals harbored a GNAQ p.R183Q variant, and two individuals harbored a GNA11 p.R183C variant. All individuals had extensive cutaneous CMs involving the trunk and covering 9%–56% of their body surface area. The median age of hypertension diagnosis was 15 years (range 11–24 years), with three individuals having renal abnormalities on imaging. Conclusions: Early‐onset hypertension is associated with extensive CMs harboring somatic variations in GNAQ/11 . Here, we expand on the GNAQ/11 phenotype and hypothesize potential mechanisms driving hypertension. We recommend serial blood pressure measurements in patients with extensive CMs on the trunk and extremities to screen for early‐onset hypertension.